The Unexpected Late Complication due to Spilled Gallstones: Collect as Much as Possible the Next Time - Fatih Başak; Erdem Kınacı; Oğuzhan Dinçel; Acar Aren (İstanbul Medical Journal, 2016)

(untitled)
Spillage of bile and gallstones has been reported in the literature with an incidence of 6% of all laparoscopic cholecystectomies. This spillage can act as a septic focus and cause various complications. We present the case of a patient with abdominal and flank abscesses 10 years after laparoscopic cholecystectomy. The abscesses were drained by the percutaneous method under the guidance of ultrasound. No laparotomy or further treatment was needed. In the etiology of unexpected abdominal or flank abscess, abscesses due to dropped gallstones should be considered as a possible diagnosis in patients having a history of previous laparoscopic cholecystectomy. Surgeons must pay careful attention and collect as many dropped gallstones as possible during laparoscopic cholecystectomy.